2024
DOI: 10.20944/preprints202402.1209.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Association Study of Seed Morphology-Related TRAITS in Sorghum Mini Core and Senegalese Lines

Ezekiel Ahn,
Sunchung Park,
Zhenbin Hu
et al.

Abstract: Sorghum (Sorghum bicolor L.) ranks fifth as the most crucial cereal crop globally, yet its seed morphology remains relatively unexplored. This study investigated seed morphology in sorghum based on 115 mini core and 130 Senegalese germplasms. Eight seed morphology traits encompassing size, shape, and color parameters were assessed. Statistical analyses explored potential associations between these traits and resistance to three major sorghum diseases: anthracnose, head smut, and downy mildew. Furthermore, geno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
0
2
Order By: Relevance
“…By analyzing 153 Senegalese sorghum accessions, we uncovered novel links between seed morphology and the newly identified P5 strains of S. reilianum, with stronger susceptibility observed in larger seeds. This finding contrasts with our study in sorghum mini core lines [25] but highlights potential germplasm-specific variation in seed size-susceptibility relationships. Notably, systemic syringe inoculation exhibited only a weak linkage to seedling spot appearance, suggesting diverse defense mechanisms throughout sorghum growth, as outlined by Craig and Frederickson [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By analyzing 153 Senegalese sorghum accessions, we uncovered novel links between seed morphology and the newly identified P5 strains of S. reilianum, with stronger susceptibility observed in larger seeds. This finding contrasts with our study in sorghum mini core lines [25] but highlights potential germplasm-specific variation in seed size-susceptibility relationships. Notably, systemic syringe inoculation exhibited only a weak linkage to seedling spot appearance, suggesting diverse defense mechanisms throughout sorghum growth, as outlined by Craig and Frederickson [17].…”
Section: Discussioncontrasting
confidence: 99%
“…The correlation study showed a positive correlation between seed size and the P5 incidence rate, indicating increased susceptibility (Table 2). This contradicts our recent findings in a sorghum mini-core line study [25]. This discrepancy may stem from several possibilities, including using different sorghum accessions, distinct P5 pathotypes, or potential human error during manual inoculation.…”
Section: Discussioncontrasting
confidence: 99%